Kanały dystrybucji produktów bankowych dla rolników indywidualnych - Szafrańska, Monika (Distribution Channels of the Banking Products for Individual Farmers, 2005)
The aim of the article is to present the kinds and the degree of utilization distribution channels of the banking products for individual farmers. The final sample consists of 156 farmers of Cracow powiat. The main marketing channel is direct sale (98,5%). There is sale in branches, telephones and internet banking, agents of the banks and cash machines. Almost 2,0% of distribution channels there, are indirect channels.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1070, t. 2, s. 316-320